Psychological characteristics of an adult’s attitude towards money - DOVBYK, Zhanna; MIKUNOV, Andriy (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. This study explores the core psychological traits of adults’ attitudes toward money. These attitudes combine both rational and emotional elements, where money serves not just as a means of purchase but also as a symbol of security, control, status, and personal self-fulfillment. Social, psychological, and economic factors, including financial literacy and social status, influence changes in these attitudes. Methods. The research used both theoretical and empirical methods, along with psychodiagnostic tools: the «Money Beliefs and Behavior Scale» (A. Furnham) and the «Monetary Ethics Scale» (E. Tang). Results. Gender differences were identified: men more frequently exhibit emotionally driven, status-oriented, and risk-prone attitudes toward money, perceiving it as a symbol of power and self-actualization, along with higher impulsivity. In contrast, women tend to be more rational, focusing on stability and long-term security, with a lower propensity for risky behavior. Both genders recognize money as an essential factor of influence, yet men attribute more status-related significance to it, while women emphasize its practical value. Age-related differences reflect the evolution of financial consciousness, where young people tend to exhibit a more emotional and symbolic attitude toward money as a sign of status and freedom. With age, money gains a functional significance as a means of stability and control. Among older age groups, there is a heightened awareness of the potential moral ambiguity of money, highlighting its ambivalent nature as both a necessary resource and a source of social and ethical challenges. Conclusions. Attitudes toward money constitute a complex socio-psychological phenomenon shaping financial behavior, motivation, and self-esteem, especially under conditions of social instability, such as war. Money serves not only as a means of consumption but also as a symbol of security, control, status, and self-realization; it fulfills needs and symbolizes social respect and freedom. This attitude is influenced by social, psychological, and economic factors, including financial literacy and social status, which impact adults’ choices of financial strategies. Considering these features is essential for developing effective financial strategies and educational programs.